THE IMPACT OF LISTEN TO THE VOICE OF THE CUSTOMER IN ACHIEVING COMPETITIVE SUPERIORITY - جثير, سعدون حمود; سعيد, سارة علي (Journal of Economics and Administrative Sciences, 2012)
The subject of the listen to the voice of the customer of topics relatively new in management thought, as it won the attention of many organizations of different types, because it is important to achieve success and to continue and superiority to them, so there is a need to study this term in the Iraqi organizations and try to diagnose the implementation of the study sample to listen voice of the Customer and its impact in achieving the competitive superiority.The study sample consisted of a group of workers in the company Zain and Asia Cell Telecommunications have been using the questionnaire as a tool for data collection, as numbered (109) by (49) of Zain Telecom and (60) for the Asia-Cell Telecom. The study found the existence of significant differences in listen to the voice of the customer between the two companies examined, and there for provided a set of recommendations.